TGFBR2‑dependent alterations of microRNA profiles in extracellular vesicles and parental colorectal cancer cells - Fricke, Fabia; Mussack, Veronika; Buschmann, Dominik; Haußer-Siller, Ingrid; Pfaffl, Michael W.; Kopitz, Jürgen; Gebert, Johannes (International journal of oncology, 2019)
In colorectal cancer (CRC) with microsatellite instability (MSI), >90% of cases are affected by inactivating frameshift mutations of transforming growth factor β receptor type 2 (TGFBR2). TGFBR2 deficiency is considered to drive MSI tumor progression by abrogating downstream TGF‑β signaling. This pathway can alter the expression of coding and non‑coding RNAs, including microRNAs (miRNAs), which are also present in extracellular vesicles (EVs) as post‑transcriptional modulators of gene expression. In our previous study, it was shown that TGFBR2 deficiency alters the protein composition and function of EVs in MSI tumors. To investigate whether mutant TGFBR2 may also affect the miRNA cargo of EVs, the present study characterized miRNAs in EVs and their parental MSI tumor cells that differed only in TGFBR2 expression status. The HCT116‑TGFBR2 MSI cell line model enables the doxycycline (dox)‑inducible reconstituted expression of TGFBR2 in an isogenic background (‑dox, TGFBR2 deficient; +dox, TGFBR2 proficient). Small RNA sequencing of cellular and EV miRNAs showed that the majority of the miRNAs (263/471; 56%) were shared between MSI tumor cells and their EVs. Exploratory data analysis revealed the TGBFR2‑dependent cluster separation of miRNA profiles in EVs and MSI tumor cells. This segregation appeared to result from two subsets of miRNAs, the expression of which were regulated in a TGFBR2‑dependent manner (EVs: n=10; MSI cells: n=15). In the EV subset, 7/10 miRNAs were downregulated and 3/10 were upregulated by TGFBR2 deficiency. In the cellular subset, 13/15 miRNAs were downregulated and 2/15 miRNAs were upregulated in the TGFBR2‑deficient cells. The present study emphasizes the general overlap of miRNA profiles in MSI tumor cells and their EVs, but also highlights the impact of a single tumor driver mutation on the expression of individual miRNAs, as exemplified by the downregulation of miR‑381‑3p in TGFBR2‑deficient MSI tumor cells and their secreted EVs.
Gesehen am 09.12.2019